The Effect of Leadership Style, Work Motivation and Salary on Employee Performance at The Pratama Clinic of Dr.X - Christiyanti, Priscadella Putri; Sukatmadiredja, Noneng R.; Kusumaningtyas, Menur (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The purpose of this study was to reveal the extent to which leadership style, motivation, and salary influence employee performance at the dr.X primary clinic. The research method is a descriptive quantitative approach. The sample taken was 18 respondents. In data collection using online questionnaires and direct observation. Data analysis techniques using SPSS. The findings of the study indicate that employee performance increased significantly due to the positive impact of leadership style, motivation, and salary.